Academic spin doctoring: The incommensurability debate as a scholarly war fantasy. Issue 4 (November 2018) - Lowe, Sid; Rod, Michel
Abstract: This commentary to Shaw and Nowicki (2018) proposes that academic paradigms are 'dialogical' discourses that both compete and collaborate in order to sustain their identities. They are all based on different underlying assumptions and are carried by different symbols, tropes and narratives. Each version of the truth cultivates an identity that principally depends upon it not being its alternative. As a result, each paradigm depends upon the continued existence of its opposite. In this sense, therefore, the paradigm wars were a concocted dispute over invented territories and contrived opponents. The contribution of the paper for those seeking paradigmatic peace is to emphasise that just as the war was a concocted 'simulacrum', any peace must also be designed as fantasies accomplished through language games. Chinese Abstract: Shaw 和 Nowicki 的这篇评论文章 (2018年) 提出, 学术范式是"对话式"话语, 为了维持他们的身份, 既可以竞争也可以合作. 他们都基于不同的基本假设, 并由不同的符号, 比喻和叙述来承载. 真理的每一个版本都会培育出一种主要依赖于它而不是其替代品的身份. 因此, 每个范式都要依赖于它的对立面的持续存在. 因此, 在这个意义上, 范式战争是对虚构领土和人为对手的编造争论. 该论文对那些寻求范式和平者的贡献是强调, 正如范式战争是一个炮制的"假象", 任何和平也都必须设计为通过语言游戏实现的幻想.